Effects of project risk management strategies on project performance - Thilakarathna, R.D.G.N.M.; Mathivathany, S. (University of Jaffna, 2020)
Risk is an unavoidable phenomenon that may potentially interfere with the successful completion of a project. It may affect positively or negatively to the cost, quality and duration of any of the projects. In traditionally, project managers consider negative risk management strategies, but lack of consideration is about positive risk management strategies. From the initial stage through completion, Project should have an adopted and updated risk management process to respond to the risk. The research aims to identify the risk management strategies and their effects on project performance by especially referring to the road construction projects of the road development authority in Sri Lanka. The researcher adopted the qualitative method and used interviews with responsible professionals and documentary reviews to collect necessary data and information. The research results mainly identified types of risks, risk management practices in the road construction project and risk management strategies. The financial risk was very high in the road construction project and lack of risk management practices and strategies. Professionals from the RDA should be adapted proactive and efficient action with responsible and tactful risk management teams.
Keywords: Project performance; Risk management strategies and road construction project